Peranan Kepercayaan Terhadap Tuhan Yang Maha Esa Dan Kepatuhan Sosial Dalam Meningkatkan Disiplin Waktu Sholat Pada Masyarakat Pedesaan - Risman Risman (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This study aims to analyze the role of belief in God Almighty and social obedience in improving prayer time discipline in rural communities. Discipline in prayer time reflects faith and social awareness of religious values ​​prevalent in the community. The research method used was a descriptive qualitative approach through interviews and observations of rural communities with an Islamic religious background. The results show that a strong belief in God Almighty encourages individuals to be more consistent and punctual in performing prayers. Furthermore, social norms and pressures in rural communities play a significant role in shaping collective adherence to prayer times. The combination of spiritual awareness and social obedience creates religious harmony that strengthens the community's discipline in carrying out religious obligations.